The genesis of technoscientific revolutions rethinking the nature and nurture of research - Narayanamurti, Venkatesh, 1939- (Harvard University Press, 2021)
"Scientific progress doesn't always precede engineering advances; it often follows. Answering questions isn't always the goal; finding questions often is. Sometimes we seek to strengthen conventional wisdom; sometimes to surprise it. What if we could rethink nurturing research, through policy and management, to harmonize with the nature of research?"--